2016
DOI: 10.1088/1538-3873/128/962/045004
|View full text |Cite
|
Sign up to set email alerts
|

Comparing NEO Search Telescopes

Abstract: Multiple terrestrial and space-based telescopes have been proposed for detecting and tracking near-Earth objects (NEOs). Detailed simulations of the search performance of these systems have used complex computer codes that are not widely available, which hinders accurate cross-comparison of the proposals and obscures whether they have consistent assumptions. Moreover, some proposed instruments would survey infrared (IR) bands, whereas others would operate in the visible band, and differences among asteroid the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
0
10
3
Order By: Relevance
“…The distribution of V magnitudes turns over sharply at V ∼ 23.5 − 23.75. This is inconsistent with Figure 7 in Myhrvold (2016), who assumes 50% limiting magnitudes ∼ 0.8 mag fainter than our computations indicate.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The distribution of V magnitudes turns over sharply at V ∼ 23.5 − 23.75. This is inconsistent with Figure 7 in Myhrvold (2016), who assumes 50% limiting magnitudes ∼ 0.8 mag fainter than our computations indicate.…”
Section: Resultscontrasting
confidence: 99%
“…The limiting magnitudes and solar elongation coverage presented here are at odds with Myhrvold (2016); his Figure 7 shows much fainter limiting magnitudes than presented here. While Myhrvold (2016) cites the possibility and capability of LSST observing at much smaller solar elongations, this is inconsistent with the published cadences provided by the LSST project and would potentially interfere with its other science goals. Additionally, Myhrvold (2016) incorrectly assumes that an object need only be detected once for it to be counted as discovered, cataloged, and tracked.…”
Section: Lsst Survey Patternscontrasting
confidence: 67%
See 1 more Smart Citation
“…It is, however, possible to approximate it using the so-called standard H, G magnitude system (Bowell et al 1989). In this system, the phase function of a general asteroid is empirically determined, and the Bond albedo for a Lambertian sphere with phase correction is written as (8) Although Bowell et al (1989) Myhrvold (2016) found that the best fitting function had (C 1 , C 2 ) = (0.286, 0.656). We confirmed the latter result and used it throughout this study.…”
Section: Parameter Relationsmentioning
confidence: 99%
“…Multi-wavelength, photometric infrared observations of asteroids provide essential information about the thermophyiscal properties of their surfaces. A handful of both simple thermal models (Harris, 1998;Lebofsky et al, 1978Lebofsky et al, , 1986Wolters and Green, 2009;Myhrvold, 2016) and more sophisticated themophysical models (TPMs; Spencer et al, 1989;Spencer, 1990;Lagerros, 1996;Delbo' et al, 2007;Mueller, 2007; have been established as effective means of modeling thermal infrared observations of asteroids. The general purpose of a thermal model is to compute surface temperatures for an object, which are in turn used to calculate the emitted flux at the desired wavelengths (see , for a recent review).…”
Section: Introductionmentioning
confidence: 99%